Pengaruh Sistem Rekrutmen dan Lingkungan Kerja Terhadap Kinerja Karyawan - Ananto Krisna Wardhana; Kaman Nainggolan; Riris Lestiowati; Rachmat Fadly (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2020)
Performance is one of the main factors demanded by every organization. The recruitment system and work environment are things that play a role in achieving employee performance at PT. HYUNDAI MOBIL INDONESIA (PT. HMI). The formulation of the problem in this study is the extent to which the influence of the recruitment system and work environment on employee performance at PT. HMI. This research was conducted at PT. HMI, the nature of quantitative causality research with survey method, where the entire population of employees of PT. HMI was used as a sample in this study. In conducting this research, the data used are primary data and secondary data. Data was collected through a questionnaire with a Likert scale unit of measurement. This research was conducted using multiple linear regression analysis method.